Impacts of anemia and its determinants among 6–59 months age children residing in Dayniile internally displaced person’s camps, Banadir region, Somalia - Abdirasak Sharif Ali Mude; Farhia Abdullahi Ali; Sumaya Hassan Ali (Iraqi Journal of Hematology)
BACKGROUND: The prevalence of anemia in children under 5 years of age is a multifaceted issue influenced by various factors, leading to diverse findings across studies. This study aimed to assess the prevalence of anemia and its associated factors among children under 5 years of age living in internally displaced persons camps in the Dayniile district of Somalia. MATERIALS AND METHODS: This cross-sectional study was conducted between December 2022 and July 2023 in Mogadishu, Somalia. Blood samples from children under 5 years of age were checked for malaria and parasites, as well as for hemoglobin, erythrocytes, hematocrit, mean cell volume, and hematocrit. SPSS version 27.0.1 was used for data analysis, involving descriptive and inferential statistics. Fisher’s exact test examined anemia associations due to low expected counts. RESULTS: The prevalence of anemia among children under 5 years old was 17.6%. Anemia severity varied from mild (8.4%) to moderate (8.7%) to severe (0.5%). No significant correlation was found between a child’s primary caregiver and anemia status nor between anemia and sex, age, maternal factors, or family income sources. However, the presence of income from other relatives was statistically significant (P = 0.046*), indicating that financial support from extended family members may reduce the incidence of severe anemia in young adults. Children with a history of malaria had notably higher rates of mild and moderate anemia (25.0% and 75.0%, respectively) than those without. CONCLUSION: Our study, along with previous research, underscores the complexity of the prevalence of childhood anemia and its contributing factors. Addressing anemia in children from lower-income families and urban areas requires tailored intervention. In addition, controlling malaria and promoting breastfeeding are essential strategies for reducing the prevalence of anemia in young children. Overall, a multifaceted approach considering socioeconomic, health, and dietary factors is crucial for the well-being of children under 5 years old.